Contribution to morphology, biology and distribution of Mecolenus wahlbergi Schoenherr, 1847, a relict African apionine weevil (Coleoptera: Brentidae: Apioninae) - Wanat, Marek; Procheş, Şerban (Zootaxa, 2021)
Mecolenus wahlbergi Schoenherr, the sole member of the basal apionine tribe Mecolenini and one of the least known South African weevils, was re-discovered at a new locality at Umtamvuna River separating KwaZulu-Natal and Eastern Cape provinces. It was found feeding on leaves of the Broad-leaved Wild-quince Cryptocarya latifolia Sond. (Lauraceae), which is the first record on the biology of this species. The distribution of M. wahlbergi is summarized and mapped, including unpublished records based primarily on the specimens deposited at the Durban Natural Science Museum. Concordance between the distribution of the weevil and its putative host C. latifolia is discussed. The adult morphology of M. wahlbergi is re-described and illustrated.